+0  
 
0
381
2
avatar+1832 

which one is correct and why  

 

 

 

 

 

xvxvxv  Feb 10, 2015

Best Answer 

 #1
avatar+92669 
+10

d/dx ( sin^4/4 - sin^6/6 + C) =

sin^3x(cosx) - sin^5x(cosx) =

cosx(sin^3x)(1 - sin^2x) =

cosx (sin^3x)(cos^2x) =

sin^3xcos^3x

And           

d/dx(-cos^4x/4 + cos^6x/6 + C)=

-(sinx)(-cos^3x)   - (sinx)cos^5x  =

(sinx)(cos^3x)(1 - cos^2x) =

(sinx)(cos^3x)(sin^2x) =

(cos^3x)(sin^3x)  = sin^3xcos^3x

And they are exactly the same.....!!!

 

CPhill  Feb 10, 2015
 #1
avatar+92669 
+10
Best Answer

d/dx ( sin^4/4 - sin^6/6 + C) =

sin^3x(cosx) - sin^5x(cosx) =

cosx(sin^3x)(1 - sin^2x) =

cosx (sin^3x)(cos^2x) =

sin^3xcos^3x

And           

d/dx(-cos^4x/4 + cos^6x/6 + C)=

-(sinx)(-cos^3x)   - (sinx)cos^5x  =

(sinx)(cos^3x)(1 - cos^2x) =

(sinx)(cos^3x)(sin^2x) =

(cos^3x)(sin^3x)  = sin^3xcos^3x

And they are exactly the same.....!!!

 

CPhill  Feb 10, 2015
 #2
avatar+1832 
0

Thank you CPhill 

xvxvxv  Feb 13, 2015

29 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.